PREDICTION OF MEGATHRUST IMPACT ON SEISMIC RESPONSE IN SELEBAR DISTRICT OF BENGKULU CITY - Zhehan Fahrezi; Rena Misliniyati; Khairul Amri; Lindung Zalbuin Mase; Hardiansyah (Jurnal Pensil)
Bengkulu City was hit by major earthquakes in 2000 and 2007 with magnitudes of 7.9 Mw and 8.6 Mw. In 2022 BMKG Baai Island, Bengkulu City, said that there is a potential for an earthquake with a maximum magnitude of 8.9. This study was conducted to determine the response of soil layers due to megathrust earthquake wave propagation in Selebar district, Bengkulu City. The study began with field investigations at six points. The seismic response analysis was built based on a one-dimensional wave propagation model with non-linearity. The 2007 Bengkulu-Mentawai earthquake wave with a magnitude of 8.8 Mw was applied as the input wave. PGA, acceleration response spectra, and amplification factors are presented in this study. The resulting PGA ranged from 0.328g - 0.453g. Five points experienced amplification with amplification factors of 1.093 - 1.317. The spectral acceleration has generally exceeded the applicable design spectral acceleration at a period of 0.2 seconds. The spectral accelerations have generally exceeded the applicable seismic design at short periods, with maximum values of 1.27g - 1.64g. So it is necessary to update the seismic design for building planning in Selebar District, Bengkulu City.